Characteristics of temperature uniformity system in multi-tier drying equipment with sharp turning technology - afandi, dedi; Syuhada, Ahmad; razali, razali; maulana, muhammad ilham (Jurnal Polimesin, 2024)
Drying is a process of heat and mass transfer that occurs on the surface and within the material to be dried. It helps reduce the internal moisture of the material, inhibiting the growth, damage, and chemical changes of microorganisms during storage, thus extending the shelf life of dry materials and improving the quality of raw materials. This study aims to test multi-level drying equipment using combustion heat with a square shape and racks inside it used as the drying space for the material. The raw material was placed on racks made of perforated metal. This  research started from designing the drying equipment system, fabricating and testing system. The drying system was tested using fish and cocoa beans as sample materials. The tested equipment system included temperature distribution in the combustion chamber, distribution system of hot combustion gases through sharp turning technology, uniform temperature distribution in the drying chamber with 8 levels of racks, each capable of holding a load of 10 kg, and testing of the chimney system. The research findings concluded that to maintain a drying chamber temperature of 90⁰C, an average combustion chamber temperature of 339⁰C was required. The average combustion chamber temperature needed to maintain a drying chamber temperature of 80⁰C was 290⁰C. For a drying chamber temperature of 70⁰C, an average combustion chamber temperature of 314⁰C was required. The temperature distribution inside the drying chamber moves horizontally, indicating that the temperature distribution in the drying chamber was uniform for each drying rack.